THE AGRO TOURISM SERVICE READINESS OF THE FARMER LEARNING CENTER AT BAN HOM CHUEN LADLUMKAEW DISTRICT, PATHUMTHANI PROVINCE - Reanrat, Nichakorn; Rengkounkway, Metta; Mekarkakorn, Tawica (Journal of Sports Science and Health, 2019)
Purpose The purpose of this study was 1) To explore personal basic information of the farmer learning center tourists at Ban Hom Chuen 2) To study travel behavior at the farmer learning center at Ban Hom Chuen 3) To study the service readiness of the farmer learning center at Baan Hom Chuen 4) To find the problem and suggestion from tourist and study tour group. Methods This study was quantitative research. The questionnaire were used to collect data from sample group of 389 samples. Data were analyzed by using frequency, percentage, mean and standard deviation. Results The results revealed that the most of tourists and job observation group was female. The range of age was 31 to 40 years old and graduated with a bachelor degree. Most they were the business owner and income per a moth was about 25,000 THB or more. They mostly came from Bangkok or nearby and used their own cars to go to the farmer learning center at Baan Hom Chuen. They suggested the attending activity fee should be 300 THB. Finally, they knew this farmer learning center from the internet and facebook. For the range of readiness of the farmer learning center at Baan Hom Chuen; the most readiness was activity with mean score of 4.44 (S.D.=0.61), followed by participation mean score 4.37 (S.D.=0.61), place mean score 4.20 (S.D.=0.66) and management mean score 3.84 (S.D.=0.81), respectively. Conclusion It is concluded that readiness of the farmer learning center at Baan Hom Chuen’s in 4 parts are at the place part and the management part high level and at highest level (the activity part and the participation part). However, this learning center has some problems about the imbalance between the amount of lavatory and tourism’s need and the publicity.